2022
DOI: 10.1002/pc.26810
|View full text |Cite
|
Sign up to set email alerts
|

Effect of black rice husk ash biosilica on mechanical, wear, and fatigue behavior of stacked aloevera/roselle and glass fiber reinforced epoxy composite

Abstract: In this present study, a high‐performance structural epoxy biocomposite has been prepared and characterized for its mechanical, wear, and fatigue behavior. The main aim of this research was to determine the effect of fiber stacking order and the biosilica addition in the epoxy hybrid composite when it is subjected to external loading. The research also focused on how the surface treatment process on fiber and particle affects the mechanical, wear, and fatigue behavior of composite. The biosilica particles were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Tensile strength grew linearly up to a reinforcement level of 5 wt% bentonite nanoclay, but after that it started to decline despite the reinforcement level being increased further. The ber-matrix adhesion and ber orientation are signi cant strictures that in uence the mechanical characteristics of short ber and nanoparticle reinforced polymer composites [23,24]. These ndings demonstrated that sisal bers containing bentonite nanoclay had a superior contact with polymer matrix, enabling an improved rigidity, enhanced tension sharing, and consequently improved tensile testing results.…”
Section: Tensile Strengthmentioning
confidence: 88%
“…Tensile strength grew linearly up to a reinforcement level of 5 wt% bentonite nanoclay, but after that it started to decline despite the reinforcement level being increased further. The ber-matrix adhesion and ber orientation are signi cant strictures that in uence the mechanical characteristics of short ber and nanoparticle reinforced polymer composites [23,24]. These ndings demonstrated that sisal bers containing bentonite nanoclay had a superior contact with polymer matrix, enabling an improved rigidity, enhanced tension sharing, and consequently improved tensile testing results.…”
Section: Tensile Strengthmentioning
confidence: 88%
“…In comparison to their synthetic counterpart (i.e., glass fibers [GFs], aramid fibers, or carbon fibers), natural fibers offer various advantages such as lower weight, lower cost, lower density, biodegradable, and sustainable. [1][2][3] To this end, natural fibers reinforced composites have been explored for use in several applications such as medical implants, furniture fittings, paper industries, and textile industries. [4][5][6] Plant based polymer composites are preferred as they have superior sound and thermal resistance characteristics, and higher wear resistance that provide a safe and healthy working environment.…”
Section: Introductionmentioning
confidence: 99%
“…Demand for the use of natural fibers as polymer reinforcement has increased in the last few years. In comparison to their synthetic counterpart (i.e., glass fibers [GFs], aramid fibers, or carbon fibers), natural fibers offer various advantages such as lower weight, lower cost, lower density, biodegradable, and sustainable 1–3 . To this end, natural fibers reinforced composites have been explored for use in several applications such as medical implants, furniture fittings, paper industries, and textile industries 4–6 .…”
Section: Introductionmentioning
confidence: 99%